Drug Abuse In The Perspective Of Islamic Law - Adi Priyono (CV. AFDIFAL MAJU BERKAH, 2022)
This study aims to examine drug abuse from the perspective of Islamic law. This research is library research using a normative-theological approach. The theological-normativity side lies in the norms of Islamic law (fiqh jinayah) which are derived from revelations both from the Qur'an and from the Prophet's Hadith. Because the approach in this research can be classified as revelation research. The results of this study indicate that Islamic law against drug abuse (al-mukhaddirat) are all substances that if consumed will damage the physical and the mind, sometimes even making people crazy or drunk. The basic concept of drugs in Islamic law is based on khamr in the letter al-Maidah verse 90 which is condemned to be forbidden for consumption. The prohibition of drug abuse can be understood with the naqli argument according to the sources of the Qur'an and Hadith as well as the aqli argument based on a study of the dangers of drug consumption that cause prolonged adverse effects.